Approach to the work of an ecofeminist theologian - Gloria M. Comesaña Santalices (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2002)
We present here a detailed analysis of Rosemary Radford Ruether's book Gaia and God. This work has a triple root: it is written from an ecological, theological and feminist perspective. Gaia and God addresses the ecological problem from a religious vision of the world, particularly that of the monotheistic religions and traditions that converge in Christianity. These religions and traditions are: the Hebrew religion and Greek-Hellenic philosophy, particularly Plato and Gnosticism. To all this we must add the new science in the 17th century. This represents the culmination of Western thought based on the idea of ​​a Unique Transcendental Being, God, creator of all things, who subjects his most perfect creature: the man, to whom the woman is also subjected. According to this vision, the Earth and everything that exists is at the service of man, and he must dominate it, exploit it and extract all its riches from it. It is this patriarchal vision that is deeply destructive and predatory for Gaia, the Earth, which the author proposes to recover through her proposal of an ecofeminist theology. Keywords: Theology, ecology, feminism
Keywords: Theology, ecology, feminism.